An analysis of binary microlensing event OGLE-2015-BLG-0060 - Tsapras, Yiannis; Cassan, Arnaud; Ranc, Clément; Bachelet, E.; Street, R.; Udalski, A.; Hundertmark, Markus; Bozza, V.; Beaulieu, J. P.; Marquette, J. B.; Euteneuer, Esther; Bramich, D. M.; et al. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present the analysis of stellar binary microlensing event OGLE-2015-BLG-0060 based on observations obtained from 13 different telescopes. Intensiv
Gesehen am 05.02.2020